INNOVATIVE APPROACHES TO THE CONCEPT OF ‘SMILE’ IN MODERN LINGUISTICS: CONNOTATIONS AND PRAGMATIC FUNCTIONS - Dinara Nuraliyeva Lutfulla qizi; Abduvahobova Mahina Azatovna (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article investigates the concept of “smile” in modern linguistics through innovative approaches that emphasize its semantic connotations and pragmatic functions. In contemporary linguistic theory, a smile is not merely a positive facial expression but a complex communicative phenomenon shaped by context, intention, and sociocultural factors. The aim of this research is to examine how the concept of “smile” operates as a multidimensional unit in discourse, reflecting both positive and negative meanings. The research employs qualitative interpretative analysis to investigate the semantic variability and pragmatic roles of “smile” in communicative and literary contexts. Special attention is given to its connotative range, including sincerity, politeness, irony, sarcasm, emotional concealment, and interpersonal strategy. The findings indicate that the meaning of “smile” is highly context-dependent and influenced by situational and cultural parameters.